Deteksi Penipuan: Menganalisis Fraud Hexagon untuk Mendeteksi Fraud dengan Komite Audit sebagai Variabel Moderasi - Novi Karsetio Wibowo; Hexana Sri Lastanti (Syntax Corporation Indonesia, 2024)
The aim of this research was to examine the impact of Pressure, Capability, Opportunity, Collusion, Rationalization, and Arrogance on Financial Report Fraud, with the Audit Committee serving as a moderating variable. The study utilized library research and documentation techniques for data collection, focusing on a sample of 54 real estate sector companies listed on the IDX from 2020 to 2022. Regression Analysis was employed to analyze the data, which was secondary in nature. The findings reveal the significant influence of Pressure, Opportunity, and Collusion on Financial Report Fraud, while Capability, Rationalization, and Arrogance did not exhibit a significant effect. Additionally, the Audit Committee as a moderating variable did not significantly impact the relationships between the Fraud Hexagon factors and Financial Report Fraud. These results offer new insights into the role of the Audit Committee in fraud prevention and the application of the Fraud Hexagon model in detecting financial report fraud. The study suggests further research to explore the interactions between these factors and the effectiveness of audit committees in mitigating fraud.